2023
DOI: 10.1364/ol.487676
|View full text |Cite
|
Sign up to set email alerts
|

Dammann gratings-based truly parallel optical matrix multiplication accelerator

Abstract: Matrix multiplication (MM) is a fundamental operation in various scientific and engineering computations, as well as in artificial intelligence algorithms. Efficient implementation of MM is crucial for speeding up numerous applications. Photonics presents an opportunity for efficient acceleration of dense matrix computation, owing to its intrinsic advantages, such as huge parallelism, low latency, and low power consumption. However, most optical matrix computing architectures have been limited to realizing sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The optical beams in one-dimensional (1D) and two-dimensional (2D) array formats find numerous applications in emerging fields such as microscopy [1,2], photonics [3,4], nonlinear optics [5,6], optical trapping [7], beam shaping [8], laser fabrication [9,10], etc. For instance, Pushkarev et al [6] have demonstrated arrays of nonlinear stable beams, often referred to as filament, using optical array generators such as phase plate and Dammann grating.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical beams in one-dimensional (1D) and two-dimensional (2D) array formats find numerous applications in emerging fields such as microscopy [1,2], photonics [3,4], nonlinear optics [5,6], optical trapping [7], beam shaping [8], laser fabrication [9,10], etc. For instance, Pushkarev et al [6] have demonstrated arrays of nonlinear stable beams, often referred to as filament, using optical array generators such as phase plate and Dammann grating.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhu et al [9] have demonstrated parallel fabrication capability using multifocal spots generated by a spatial light modulator (SLM) and a high numerical aperture (NA) objective lens. Ma et al [3] have demonstrated matrix multiplications of 50 pairs of 4 * 8 matrices using Dammann gratings involving digital micro-mirror arrays. The parallel multiphoton microscopy of microspheres and nanorods was also demonstrated by Gu et al [1], wherein they generated [2 × 2] multifocal arrays using an SLM.…”
Section: Introductionmentioning
confidence: 99%